Performance Comparison of a SSVEP BCI Task by Individual Stereoscopic 3D Susceptibility - Mun, Sungchul; Park, Min-Chul; Yano, Sumio (TAYLOR & FRANCIS INC, 2013)
This study aimed at investigating the differences in brain-computer interface (BCI) task performance between 2D and 3D displays depending on their individual susceptibility to stereoscopic 3D. Eleven female and 10 male participants attempted a steady-state visually evoked potential BCI navigation task in a virtual home environment with and without 3D views. Participants were categorized into fatigued and unfatigued groups, depending on their individual susceptibility to 3D, which was characterized using a subjective evaluation method for 3D visual fatigue. The task completion time for the fatigued group under the 3D conditions was significantly delayed relative to the 2D mode. In contrast, a significantly decreased completion time was observed in the 3D view relative to the 2D view for the unfatigued group. The averaged positive predictive value significantly increased in the 3D mode relative to the 2D one for the unfatigued group only. These results are expected to provide a practical implication for enhancing BCI task performance in light of individual vulnerability to 3D.
Keywords: BRAIN-COMPUTER INTERFACE; USER EXPERIENCE; VISUAL FATIGUE; VISUALIZATION; 2D; MOTIVATION; MOTION